Volunteer Beneran Indonesia:Keterlibatan dan Komitmen Warga Negara Muda di dalam Komunitas Berlatar Belakang Multikultural - Adha, Muhammad Mona; Ulpa, Eska Prawisudawati; Budimansyah, Dasim; Johstone, Jack McGregor (Universitas Negeri Malang, 2019)
This paper aims to find out the involvement of Beneran Indonesia volunteers in the civic education program. For strengthening social cohesion, participants who are from various religions, ethnicities, and cultural backgrounds have brought together and collaborated with volunteers through this program. Qualitative research with a case study method carried out by collecting data from 14 respondents. The result of the study shows that volunteering activities create solidarity, tolerance, communication, interaction, and good connections between volunteers. This research can be used as material for further research on volunteers and students (participants) in outdoor activities to create harmonious social cohesion.